Factors influencing community college students’ educational attainment as future teachers - Gutierrez, Shellie (Kansas State University, 2006)
The goal of this research study was to identify the factors that influence community college students’ educational attainment as future teachers. In this naturalistic case study, three forms of data collection were used to answer the research question: 1) documents and reports; 2) student surveys; and 3) student interviews. The case for this study was the teacher preparation program at a mid-sized community college, Butler Community College (Butler), in El Dorado, Kansas. The population of the study included 83 elementary education majors enrolled in the teacher preparation program at the community college. Document and report analysis provided a detailed description of the teacher preparation program at Butler Community College, to include Butler’s role in teacher education. Survey analysis provided a demographic profile of the research population, as well as the barrier and support factors that influenced the educational attainment of these elementary education students. Interviews were conducted with a select group from the population (22 students) who had completed all of the education courses at Butler Community College and were ready to transfer to a four-year teacher education program. Interview analysis provided a detailed demographic profile of participants, as well as a more detailed description of the specific barriers and supports elementary education students experienced while attending Butler. The barriers and support factors were categorized as: 1) institutional barriers or supports; 2) instructional barriers or supports; and 3) personal barriers or supports. The greatest barriers students experienced were personal barriers, such as time management and financial issues. The major institutional barrier was lack of staff support, primarily advising support. Instructional barriers, such as the irrelevance of general education curriculum or problems with a specific course curriculum, were only minor barriers for students. The greatest overall support students experienced at the community college was in the form of instructional support, both faculty support and practical education coursework with accompanying field experiences. The major institutional support was staff support, namely, advising. Family support was cited as the major personal support.
Keywords: Teacher preparation at the community college; Community college role in teacher education; Educational attainment of future teachers; Persistence of future teachers; Recruitment and retention of future teachers; Education, Community College (0275); Education, Teacher Training (0530)